Direct Observational Evidence of Altered Mesosphere Lower Thermosphere Mean Circulation From a Major Sudden Stratospheric Warming. Issue 7 (10th April 2023) - Gasperini, Federico; Jones, McArthur; Harding, Brian J.; Immel, Thomas J.
Abstract: Sudden stratospheric warmings (SSWs) are large‐scale phenomena characterized by dramatic dynamic disruptions in the stratospheric winter polar regions. Previous studies, especially those employing whole atmosphere models, indicate that SSWs have strong impacts on the circulation of the mesosphere lower thermosphere (MLT) and drive a reversal in the mean meridional circulation (MMC) near 90–125 km altitude. However, the robustness of these effects and the roles of SSW‐induced changes in global‐scale wave activity to drive the reversal have been difficult to observe simultaneously. This work employs horizontal lower thermospheric (∼93–106 km altitude) winds near 10°S‐40°N latitude from the Michelson Interferometer for Global High‐resolution Thermospheric Imaging instrument onboard the Ionospheric Connection Explorer (ICON) to present observational evidence of a prominent MLT MMC reversal associated with the January 2021 major SSW event and to demonstrate connections to semidiurnal tidal activity and possible associations with a ∼3‐day ultra‐fast Kevin wave. Plain Language Summary: The winds in the mesosphere lower thermosphere (MLT) are strongly impacted by dramatic changes in the stratospheric winter polar regions associated with Sudden stratospheric warmings (SSWs). Models have shown that the climatological direction of the MLT north‐south and vertical circulation, characterized by equatorward flow near ∼100–120 km and poleward flow near ∼80–100 km, reverses following the onset of SSWs. Yet, the impacts and causes of these dynamical effects are not well established observationally due to the lack of comprehensive global measurements of the MLT region. This study evaluates the evolution of MLT winds and associated tidal and ultra‐fast Kevin wave variations during the January 2021 SSW using horizontal wind observations from the Michelson Interferometer for Global High‐resolution Thermospheric Imaging instrument onboard the Ionospheric Connection Explorer to present observational evidence of a large MLT north‐south wind reversal due to the SSW and associated global‐scale wave influences. Key Points: A prominent (∼30 m/s) reversal in the mesosphere lower thermosphere (MLT) mean meridional circulation during the January 2021 major sudden stratospheric warming (SSW) is observed in Michelson Interferometer for Global High‐resolution Thermospheric Imaging winds Strong (∼45 m/s) MLT westward flow enhancements and latitudinal (10S–40N) dependencies in the wind response occur as a result of the SSW Amplification in MLT SW2 and ultra‐fast Kevin wave1 zonal wind amplitudes are consistent with the observed westward flow enhancements